Agronomy Field Information Management System (AgroFIMS) - CGIAR Platform for Big Data in Agriculture (2019)
AgroFIMS has been subjected to user testing and iterative refinement, and a v.1.0 is available for wide use. The AgroFIMS code is also available on GitHub.